ANALISA NET PROFIT MARGIN PEDAGANG SAYUR DAN UMBI-UMBIAN DI TANAH PAPUA - Sarah Usman (Faculty of Economics and Business, Universitas Malikussaleh, 2018)
Manokwari peoples activities and papua generally is simple. Local people in their daily activities engage in activities to meet their daily needs, by doing work that is close to the culture of the local community. Sale activities of self-managed garden products can be seen in traditional markets, or along the roads outside of Manokwari. Extensive agricultural land and mixed with the fertile land of Papua, making crops of local communities fertile and can have economic value that can use to local communities daily needs, whether the result of the garden is their consumption or to sale. Seen from the land and profession of most indigenous Papuans is gardening. So the activity of papua people is bringing garden product to the market for sale and gets income. The purpose of research is to find out how much the product cost, how big the results of sales, how big Net Income and how much Net profit margin. Sample Method in this study is simple random sampling where 15 respondents of local traders who are in Sanggeng traditional markets and 15 respondents traders in Wosi traditional market taken with random. Data is taken based on interviews with questionnaire. Questionnaire contains data requirement from respondent that is income and cost. the data analysis method is Profitability with Net profit margin Analysis. Net profit margin is 69.2% means that the profit generated is 69.2% of the overall sales, every month every trader. This is because that 30.8% is all cost used of the total sales. Result of the Net profit margin means that the business of trading vegetables and tubers is potentially to increase income for the papua people.